K-pop and J-pop Influences to University Students in Malang, East Java – Indonesia : A Comparative Public Diplomacy Studies - Tonny Dian Effendi (Department of International Relations, Universitas Andalas)
This paper discussing the comparison of Korean Pop Culture and Japan Pop Culture to the youth in Malang.One of the important of this research is about public diplomacy using pop culture which creating many fans and lovers. The main purpose of the research is to show how the globalization in culture has influencing the youth in developing country like Indonesia. Malang is one of the city that have many K-Pop lovers and J-Pop lovers. This research is qualitative and using depth interview to get information from the participant as the member of the pop lovers. The result shows that both Korea and Japan's government have role on their public diplomacy by using this pop culture. They are often held the events like competition on music, dance and another shape of pop culture. J-pop has more focus on the animation (anime), cartoon (manga) and costume-player (cosplay). Whereas K-pop has more focus on the drama movie and music. From observation to the pop lovers, the J-pop lovers is more creative because they have a challenge, especially for cosplay to create their own costume to the competition. But for K-pop, they are more focused to learn and imitate the dance style of the Korean artist. But, both of them have significant influence to the options for the university students in Department of International Relations, University of Muhammadiyah Malang to choose Japanese and Koreans as their subject as the third language after Bahasa Indonesia and English.